Pemberdayaan Wanita Petani Melalui Partisipasi dan Kapasitas di Kawasan Wisata Kambo - Muhammad Zainal Syafruddin; Adi Riyanto Suprayitno; Sapar Sapar; Marhani Marhani; Sri Mulia Dea; Andi Suprianto (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2025)
Introduction: Empowering female farmers in tourist areas is important to strengthen personal potential, collaboration skills, and sustainable agriculture. This study investigates the role of participation and capacity building in empowering women farmers in the Kambo tourist area. Objective: The study aims to examine how capacity building and involvement affect women farmers' empowerment. Variables studied include participation and capacity enhancement as free variables (X) and freedom as bound variables (Y). Methodology: